A Malaysian National Prerogative: engaging West Asia for long-term energy dealsand co-operation - Sabar Bin Md Hashim (Institut Kajian Rantau Asia Barat, 2010)
An enhanced Malaysia-West Asia (Middle-east) relationship is vital especially in ensuring steady import stream of energy resources in coming decades to Malaysia in light of Malaysia becoming a net oil importer after 2015. Malaysia has been identifying options to diversify its energy resources so that it would not be too dependent on the depleting gas resources and imports of coal in its energy mix. As Middle-east has strong influence in determining future development in world petroleum industry, Malaysia should position itself to leverage on traditional relationship to benefit from long-term energy deals (eg. liquefied natural gas (LNG) for post-2020 scenario). To reciprocate, Malaysia could participate in more energy infrastructure projects to leverage on the success of RM9bn Shuaybah power and water desalination privatization project in Saudi Arabia. Malaysia could also offer technical services training and industrial attachment opportunities in electricity (Institut Latihan Sultan Ahmad Shah (ILSAS), TNB) and petroleum (Universiti Teknologi PETRONAS (UTP)) to West Asian energy industry.